2004
DOI: 10.1093/nar/gkh502
|View full text |Cite
|
Sign up to set email alerts
|

Distinct requirements for Ku in N nucleotide addition at V(D)J- and non-V(D)J-generated double-strand breaks

Abstract: Loss or addition of nucleotides at junctions generated by V(D)J recombination significantly expands the antigen-receptor repertoire. Addition of nontemplated (N) nucleotides is carried out by terminal deoxynucleotidyl transferase (TdT), whose only known physiological role is to create diversity at V(D)J junctions during lymphocyte development. Although purified TdT can act at free DNA ends, its ability to add nucleotides (i.e. form N regions) at coding joints appears to depend on the nonhomologous end-joining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
0
18
2
Order By: Relevance
“…Importantly, in contrast to a study based on an episomal plasmid assay (28), in a chromosomal context, we found no N-additions in KU-deficient cells after TdT addition (Figure 3B and C), except for one event out of 23 junctions (Figure 3B), which is likely to be TdT-independent because it was also observed in cells without TdT (Figure 3A, Table 1, P  = 0.7342). Taken together, these data show that N-addition at intrachromosomal I-SceI-DSBs is largely KU80-dependent.…”
Section: Resultscontrasting
confidence: 99%
“…Importantly, in contrast to a study based on an episomal plasmid assay (28), in a chromosomal context, we found no N-additions in KU-deficient cells after TdT addition (Figure 3B and C), except for one event out of 23 junctions (Figure 3B), which is likely to be TdT-independent because it was also observed in cells without TdT (Figure 3A, Table 1, P  = 0.7342). Taken together, these data show that N-addition at intrachromosomal I-SceI-DSBs is largely KU80-dependent.…”
Section: Resultscontrasting
confidence: 99%
“…Tdt is a template-independent DNA polymerase that catalyzes the addition of deoxynucleotides to the 3′-hydroxyl terminus of oligonucleotide primers. It is expressed specifically in lymphoid cells during V(D)J recombination, increasing antigen receptor diversity by adding nucleotides at the coding ends of immunoglobulin and T cell receptor gene segments [32], [33], [34] Co-transfection of cells with Tdt and meganuclease leads to a 3-fold increase in GFP-positive cells (Figure 1B, compare 1.8% to 0.6% with the meganuclease alone). However, molecular analysis of the locus revealed a 8.2-±0.14 (p<0.0005) fold increase (26.9% vs. 3.2%) in the TM frequency in the Tdt co-transfected samples.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the “N” regions generated by TdT are unusually longer when Ku80 is knocked-out compared to when it is normally expressed [152]. Since Ku80 aids in the recruitment of TdT to the site of V(D)J recombination, these knock-down experiments suggests that Ku80 also regulates the catalytic activity of TdT once it is bound to DNA [61, 153].…”
Section: Regulating the Activity Of Tdtmentioning
confidence: 99%
“…TdT activity can also be regulated indirectly by other members of the X-family of polymerases. For example, TdT and Pol μ can efficiently compete for the same DNA substrate [152]. It has subsequently been argued that both proteins, if present during V(D)J recombination, could compete for DNA ends such that Pol μ could affect the activity of TdT during “N” region synthesis [132].…”
Section: Regulating the Activity Of Tdtmentioning
confidence: 99%